Evaluation of 2,2’-dimorpholinodiethyl ether (DMDEE) in pathology, perinatal, and genotoxicity studies - Rachel Frawley; Stephanie L. Smith-Roe; Helen Cunny; Michelle C. Cora; Karr Stinson; Guanhua Xie; Suramya Waidyanatha; Barry McIntyre; Karen Cimon (Toxicology, 2026)

Application of error-corrected sequencing technologies for in vivo regulatory mutagenicity assessment - Carole L. Yauk; Anthony M. Lynch; Vasily N. Dobrovolsky; Maik Schuler; Stephanie L. Smith-Roe; Devon Fitzgerald; Jake Higgins; Naveed Honarvar; Frank Le Curieux; Shoji Matsumura; Sheroy Minocherhomji; Leslie Recio; et al. (Regulatory Toxicology and Pharmacology, 2026)

A proposed screening strategy for evaluating the genotoxicity potential of botanicals and botanical extracts - Kristine L. Witt; Jan van Benthem; Tetyana Kobets; Guosheng Chen; Olaf Kelber; Julie Krzykwa; James T. MacGregor; Nan Mei; Constance A. Mitchell; Ivonne Rietjens; Zehra Sarigol-Kilic; Stephanie L. Smith-Roe; et al. (Food and Chemical Toxicology, 2025)

Adopting duplex sequencing technology for genetic toxicity testing: A proof-of-concept mutagenesis experiment with N-ethyl-N-nitrosourea (ENU)-exposed rats - Stephanie L. Smith-Roe; Cheryl A. Hobbs; Victoria Hull; J. Todd Auman; Leslie Recio; Michael A. Streicker; Miriam V. Rivas; Gabriel A. Pratt; Fang Yin Lo; Jacob E. Higgins; Elizabeth K. Schmidt; Lindsey N. Williams; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Error-corrected next generation sequencing – Promises and challenges for genotoxicity and cancer risk assessment - Francesco Marchetti; Renato Cardoso; Connie L. Chen; George R. Douglas; Joanne Elloway; Patricia A. Escobar; Tod Harper; Robert H. Heflich; Darren Kidd; Anthony M. Lynch; Meagan B. Myers; Barbara L. Parsons; et al. (Mutation Research - Reviews in Mutation Research, 2023)

Error-corrected duplex sequencing enables direct detection and quantification of mutations in human TK6 cells with strong inter-laboratory consistency - Eunnara Cho; Carol D. Swartz; Andrew Williams; Miriam V. Rivas; Leslie Recio; Kristine L. Witt; Elizabeth K. Schmidt; Jeffry Yaplee; Thomas H. Smith; Phu Van; Fang Yin Lo; Charles C. Valentine; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Identification of environmental chemicals that activate p53 signaling after in vitro metabolic activation - Masato Ooka; Jinghua Zhao; Pranav Shah; Jameson Travers; Carleen Klumpp-Thomas; Xin Xu; Ruili Huang; Stephen Ferguson; Kristine L. Witt; Stephanie L. Smith-Roe; Anton Simeonov; Menghang Xia (Archives of Toxicology, 2022)
Currently, approximately 80,000 chemicals are used in commerce. Most have little-to-no toxicity information. The U.S. Toxicology in the 21st Century (Tox21) program has conducted a battery of in vitro assays using a quantitative high-throughput screening (qHTS) platform to gain toxicity information on environmental chemicals. Due to technical challenges, standard methods for providing xenobiotic metabolism could not be applied to qHTS assays. To address this limitation, we screened the Tox21 10,000-compound (10K) library, with concentrations ranging from 2.8 nM to 92 µM, using a p53 beta-lactamase reporter gene assay (p53-bla) alone or with rat liver microsomes (RLM) or human liver microsomes (HLM) supplemented with NADPH, to identify compounds that induce p53 signaling after biotransformation. Two hundred and seventy-eight compounds were identified as active under any of these three conditions. Of these 278 compounds, 73 gave more potent responses in the p53-bla assay with RLM, and 2 were more potent in the p53-bla assay with HLM compared with the responses they generated in the p53-bla assay without microsomes. To confirm the role of metabolism in the differential responses, we re-tested these 75 compounds in the absence of NADPH or with heat-attenuated microsomes. Forty-four compounds treated with RLM, but none with HLM, became less potent under these conditions, confirming the role of RLM in metabolic activation. Further evidence of biotransformation was obtained by measuring the half-life of the parent compounds in the presence of microsomes. Together, the data support the use of RLM in qHTS for identifying chemicals requiring biotransformation to induce biological responses.

Combined gene dosage requirement for SWI/SNF catalytic subunits during early mammalian development - Stephanie L. Smith-Roe; Scott J. Bultman (Mammalian Genome, 2013)